Analisis Yuridis Pelindungan Hukum Merek Terkenal Untuk Barang Dan Jasa Tidak Sejenis : Studi Kasus Putusan Mahkamah Agung Nomor 29/Pk/Pdt.Sus-Hki/2016 - Fauza Qadriah (USU LAW JOURNAL, 2019)
Abstract. The results of the research indicate that, protection of trademarks of goods and / or services of the same type is regulated in Article 6 paragraph (2) of Law Number 15 Year 2001 concerning Trademarks and Article 21 of Law Number 20 Year 2016 concerning Trademarks and Geographical Indications. The articles explain that the application can be rejected if an application for the mark has similarities with another party's famous brand for similar goods, and the regulation can also apply to non-similar goods. However, the Government Regulation as the implementing regulation did not appear until 2016, resulting in several disputes that ended with the protection of famous brand owners. Decisions about similar cases have different results due to differences in views between judges in each dispute. moreover, the Supreme Court has issued SEMA Number, 03 / BUA.6 / HS / SP / XII / 2015 regarding the application of the results of the 2015 Supreme Court's plenary meeting as a guideline for the execution of duties for the court that reads "Claims for cancellation of brands that have similarities in principle or in whole with another party's trademark for goods or services that are not of the same type, the ruling is that the Lawsuit cannot be accepted. Keywords: legal protection, trademark, intellectual property rights